Diaphragm and preparation method thereof, battery and electric device

By using a lithium titanium aluminum-phosphate layer and a ceramic layer in the lithium-ion battery separator and adding an adhesive layer, the problem of ceramic coating increasing the internal resistance of the battery is solved, and the battery safety and electrical performance are improved.

CN119725998AInactive Publication Date: 2025-03-28WUXI QIAODE NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869582.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators improve thermal stability and mechanical strength through ceramic coating, but lead to increased internal resistance of the battery, reducing rate performance and long-term circulation performance.

Method used

The separator structure is adopted including a base film, a lithium titanium aluminum phosphate layer and a ceramic layer. The lithium titanium aluminum phosphate layer contains a high content of binder, and the thickness of the ceramic layer is controlled between 1 μm and 3 μm, and the first and second binder layers are added to improve the electrode contact density.

Benefits of technology

It improves the overall tensile strength and heat shrink resistance of the battery separator, reduces the short circuit area in the positive and negative electrodes, improves the rate performance and long-term circulation performance of the battery, and ensures the safety performance and manufacturing pass rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725998A_ABST
    Figure CN119725998A_ABST
Patent Text Reader

Abstract

The invention discloses a diaphragm and a preparation method thereof, a battery and a power utilization device, the diaphragm comprises a base membrane, a titanium aluminum lithium phosphate layer and a ceramic layer, one side of the base membrane is coated with the titanium aluminum lithium phosphate layer, and the other side of the base membrane is coated with the ceramic layer; the titanium aluminum lithium phosphate layer comprises the following components in percentage by mass: 40-70% of titanium aluminum lithium phosphate particles, 3-15% of a conductive agent and 25-50% of a binder. The lithium titanium aluminum phosphate layer in the diaphragm has the advantages of high ionic conductivity and wide electrochemical window, and also has good heat resistance and mechanical strength, so that the safety performance of the battery is improved, and the electrical performance of the battery is also considered; the titanium-aluminum-lithium phosphate layer contains a high-content binder, and the binder can not only bond powder inside the coating, but also enable the titanium-aluminum-lithium phosphate layer to be in close contact with a pole piece in the diaphragm in the battery manufacturing process, so that wrinkling of the battery pole piece and poor interface contact after winding are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a diaphragm and a preparation method thereof, a battery and an electrical device. Background Art

[0002] Compared with traditional batteries, lithium-ion batteries have the advantages of small size, light weight, long service life and good environmental protection. Therefore, they are widely used in electronic products, power and energy storage and other fields. The diaphragm is one of the important components of lithium-ion batteries. It mainly isolates the positive and negative electrodes to prevent internal short circuits, insulates electrons and conducts ions. The performance of the diaphragm has a great influence on the safety and electrical properties of the battery. At present, ceramic coating is often used to improve the thermal stability and mechanical strength of the diaphragm, thereby improving the safety performance of the battery cell. However, ceramic coating will increase the internal resistance of the battery, reduce the rate performance and long-term cycle performance of the lithium-ion battery, that is, reduce the electrical performance of the battery. Summary of the invention

[0003] Based on this, it is necessary to provide a diaphragm and a preparation method thereof, a battery and an electrical device, wherein the diaphragm can improve the safety performance of the battery while also enabling the battery to have good electrical performance.

[0004] In a first aspect of the present application, a diaphragm is provided, comprising a base film, a lithium titanium aluminum phosphate layer and a ceramic layer, wherein the lithium titanium aluminum phosphate layer is coated on one side of the base film, and the ceramic layer is coated on the other side of the base film;

[0005] The lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 40% to 70% of lithium titanium aluminum phosphate particles, 3% to 15% of a conductive agent, and 25% to 50% of a binder.

[0006] The lithium aluminum titanium phosphate layer in the separator of the present application not only has the advantages of high ion conductivity and wide electrochemical window, but also has good heat resistance and mechanical strength, which can improve the battery safety performance while taking into account the battery electrical performance.

[0007] The lithium titanium aluminum phosphate layer of the present application contains a high content of binder, which can not only bond the powder inside the coating, but also enable the lithium titanium aluminum phosphate layer to be in close contact with the electrode in the diaphragm during the battery manufacturing process, thereby avoiding the problems of wrinkling of the battery electrode and poor interface contact after winding, thereby improving the battery safety and electrical performance, and also improving the battery manufacturing qualification rate.

[0008] The diaphragm of the present application can reduce the coating thickness while ensuring the performance of the battery cell, ensuring the electrolyte retention amount of the long-cycle battery cell, thereby improving the electrical performance of the battery.

[0009] The diaphragm of the present application improves the overall tensile strength of the battery diaphragm. The diaphragm is pulled to both sides at the moment of needle puncture, which reduces the short-circuit area in the positive and negative electrodes to a certain extent. Moreover, the diaphragm of the present application improves the heat shrinkage resistance of the diaphragm, further reducing the short-circuit area. In addition, the diaphragm of the present application also has excellent ionic conductivity and chemical stability, can work stably in high temperature environment, and has excellent battery cell rate performance and long-term cycle performance.

[0010] In some embodiments, the lithium titanium aluminum phosphate layer includes the following components in percentage by weight: 45% to 65% of lithium titanium aluminum phosphate particles, 4% to 15% of a conductive agent, and 30% to 50% of a binder.

[0011] In some embodiments, the lithium aluminum titanium phosphate layer has a thickness of 1 μm to 3 μm.

[0012] The second aspect of the present application provides a diaphragm, including a base film, a lithium titanium aluminum phosphate layer, a ceramic layer and a first adhesive layer, the lithium titanium aluminum phosphate layer is coated on one side of the base film, and the ceramic layer is coated on the other side of the base film; the lithium titanium aluminum phosphate layer is located between the base film and the first adhesive layer, and the lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 70% to 90% of lithium titanium aluminum phosphate particles, 5% to 15% of a conductive agent and 5% to 15% of an adhesive.

[0013] The lithium aluminum titanium phosphate layer in the separator of the present application not only has the advantages of high ion conductivity and wide electrochemical window, but also has good heat resistance and mechanical strength, which can improve the battery safety performance while taking into account the battery electrical performance.

[0014] The diaphragm of the present application also includes a first adhesive layer, and the lithium titanium aluminum phosphate layer is located between the base film and the first adhesive layer. Compared with the lithium titanium aluminum phosphate layer directly contacting the electrode, adding the first adhesive layer on the surface of the lithium titanium aluminum phosphate layer can make the battery diaphragm and the negative electrode more tightly combined after hot pressing, and the inside of the winding core is smoother, which improves the safety performance while also ensuring the manufacturability and electrical performance of the battery cell.

[0015] The diaphragm of the present application can reduce the coating thickness while ensuring the performance of the battery cell, ensuring the electrolyte retention amount of the long-cycle battery cell, thereby improving the electrical performance of the battery.

[0016] The diaphragm of the present application improves the overall tensile strength of the battery diaphragm. The diaphragm is pulled to both sides at the moment of needle puncture, which reduces the short-circuit area in the positive and negative electrodes to a certain extent. Moreover, the diaphragm of the present application improves the heat shrinkage resistance of the diaphragm, further reducing the short-circuit area. In addition, the diaphragm of the present application also has excellent ionic conductivity and chemical stability, can work stably in high temperature environment, and has excellent battery cell rate performance and long-term cycle performance.

[0017] In some embodiments, the lithium aluminum titanium phosphate layer has a thickness of 1 μm to 2.5 μm.

[0018] In some embodiments, the ceramic layer includes the following components in percentage by weight: 65% to 82% of ceramic, 3% to 10% of conductive agent, and 15% to 25% of binder.

[0019] In some embodiments, the diaphragm also includes a second adhesive layer, the ceramic layer is located between the base film and the second adhesive layer, and the ceramic layer includes the following components in percentage by mass: 87% to 94% ceramic, 1% to 3% conductive agent and 5% to 10% adhesive.

[0020] In some embodiments, the thickness of the ceramic layer is 1 μm to 3 μm.

[0021] In some embodiments, the thickness of the ceramic layer is 2 μm to 4 μm.

[0022] In some embodiments, the thickness of the first adhesive layer is 0.5 μm to 2 μm.

[0023] In some embodiments, the thickness of the second adhesive layer is 0.5 μm to 2 μm.

[0024] In some embodiments, the material of the first adhesive layer includes one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid and polyvinyl alcohol.

[0025] In some embodiments, the material of the second adhesive layer includes one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid and polyvinyl alcohol.

[0026] The third aspect of the present application provides a method for preparing a diaphragm, comprising the following steps:

[0027] Calculated by mass percentage, 40% to 70% of lithium aluminum titanium phosphate particles, 3% to 15% of a conductive agent and 25% to 50% of a binder are mixed and coated on one side of the base film to form a lithium aluminum titanium phosphate layer.

[0028] The mixed coating method is used to prepare the lithium titanium aluminum phosphate layer, which can not only improve the coating efficiency of the coating, but also reduce the coating thickness, thereby reducing the diaphragm impedance and improving the electrical performance of the battery. Moreover, after reducing the coating thickness, the liquid retention space is increased, which is beneficial to ensure the electrolyte retention volume for long cycles and further improve the electrical performance of the battery.

[0029] A fourth aspect of the present application provides a method for preparing a diaphragm, comprising the following steps:

[0030] 70% to 90% of lithium aluminum titanium phosphate particles, 5% to 15% of a conductive agent, and 5% to 15% of a binder are coated together on one side of the base film in terms of mass percentage to form a lithium aluminum titanium phosphate layer;

[0031] Then, a binder is coated on the surface of the lithium aluminum titanium phosphate layer to form a first binder layer.

[0032] A first adhesive layer is added to the surface of the lithium titanium aluminum phosphate layer of the diaphragm, and the lithium titanium aluminum phosphate layer is located between the base film and the first adhesive layer. Compared with the direct contact between the lithium titanium aluminum phosphate layer and the electrode, adding the first adhesive layer on the surface of the lithium titanium aluminum phosphate layer can make the battery diaphragm and the negative electrode more tightly combined after hot pressing, and the inside of the winding core is smoother, which improves the safety performance while ensuring the manufacturability and electrical performance of the battery cell.

[0033] The fifth aspect of the present application provides a battery, comprising a positive electrode sheet, a negative electrode sheet, and a diaphragm as described in the first aspect or the second aspect and a diaphragm prepared by the preparation method as described in the third aspect or the fourth aspect, wherein the diaphragm is located between the positive electrode sheet and the negative electrode sheet.

[0034] The sixth aspect of the present application provides an electrical device comprising the battery as described in the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the battery separator structure prepared in Example 1.

[0036] Figure 2 This is a schematic diagram of the battery separator structure obtained in Example 5.

[0037] Figure 3 This is a schematic diagram of the battery separator structure prepared in Comparative Example 1.

[0038] Figure 4 This is a schematic diagram of the battery separator structure prepared in Comparative Example 2.

[0039] Figure 5 This is a comparison diagram of the core interface after capacity division in Example 1.

[0040] Figure 6 This is a comparison diagram of the core interface after capacity division in Example 3.

[0041] Figure 7 This is a comparison diagram of the core interface after capacity division in comparative example 2.

[0042] Figure 8 This is a comparison chart of the acupuncture process of Example 1 and Comparative Example 2.

[0043] Fig. 9 It is a comparison chart of the discharge capacity retention rate during the cycle process of Example 1, Example 2 and Comparative Example 1.

[0044] Description of reference numerals:

[0045] 1. lithium aluminum titanium phosphate layer; 2. ceramic layer; 3. base film; 4. first adhesive layer; 5. second adhesive layer. DETAILED DESCRIPTION

[0046] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0048] Battery separators are an important component of lithium-ion batteries and are closely related to battery safety and electrical performance. Traditional technologies mostly use ceramic coating to improve the thermal stability and mechanical strength of separators and thus improve the safety performance of battery cells. However, traditional ceramic coatings will increase the internal resistance of batteries and reduce the rate performance and long-term cycle performance of lithium-ion batteries. Based on this, the present application is dedicated to providing a battery separator that can improve battery safety while ensuring that the battery has good electrical performance.

[0049] In a first aspect of the present application, an embodiment provides a diaphragm, comprising a base film, a lithium titanium aluminum phosphate layer and a ceramic layer, wherein the lithium titanium aluminum phosphate layer is coated on one side of the base film, and the ceramic layer is coated on the other side of the base film;

[0050] The lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 40% to 70% of lithium titanium aluminum phosphate particles, 3% to 15% of a conductive agent, and 25% to 50% of a binder.

[0051] The lithium aluminum titanium phosphate layer in the separator of the present application not only has the advantages of high ion conductivity and wide electrochemical window, but also has good heat resistance and mechanical strength, which can improve the battery safety performance while taking into account the battery electrical performance.

[0052] The lithium titanium aluminum phosphate layer of the present application contains a high content of binder, which can not only bond the powder inside the coating, but also enable the lithium titanium aluminum phosphate layer to be in close contact with the electrode in the diaphragm during the battery manufacturing process, thereby avoiding the problems of wrinkling of the battery electrode and poor interface contact after winding, thereby improving the battery safety and electrical performance, and also improving the battery manufacturing qualification rate.

[0053] The diaphragm of the present application can reduce the coating thickness while ensuring the performance of the battery cell, ensuring the electrolyte retention amount of the long-cycle battery cell, thereby improving the electrical performance of the battery.

[0054] The diaphragm of the present application improves the overall tensile strength of the battery diaphragm. The diaphragm is pulled to both sides at the moment of needle puncture, which reduces the short-circuit area in the positive and negative electrodes to a certain extent. Moreover, the diaphragm of the present application improves the heat shrinkage resistance of the diaphragm, further reducing the short-circuit area. In addition, the diaphragm of the present application also has excellent ionic conductivity and chemical stability, can work stably in high temperature environment, and has excellent battery cell rate performance and long-term cycle performance.

[0055] In some embodiments, the lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 45% to 65% lithium titanium aluminum phosphate particles, 4% to 15% conductive agent, and 30% to 50% binder. Under this component and mass ratio, the lithium titanium aluminum phosphate layer and the ceramic layer can be in close contact with the pole piece during the battery manufacturing process, avoiding the problem of wrinkling of the battery pole piece and poor interface contact after winding, thereby improving the battery safety and electrical performance. The cell needle puncture pass rate of the diaphragm made under this component and mass ratio is 100%, and the battery cycle capacity retention rate is also very high, achieving excellent safety and electrical performance.

[0056] In some embodiments, the thickness of the lithium aluminum titanium phosphate layer is 1 μm to 3 μm, preferably 1 μm to 1.5 μm.

[0057] The thickness of the lithium aluminum titanium phosphate layer can be controlled at 1μm ~ 3μm, which reduces the coating thickness while ensuring the performance of the battery cell, leaving room for retaining the electrolyte in long-cycle batteries.

[0058] As an example, the thickness of the lithium aluminum titanium phosphate layer can be 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm and 3.0μm, or it can be within the range formed by any two of the above point values ​​as end values.

[0059] In some embodiments, the thickness of the lithium titanium aluminum phosphate layer is 1 μm to 1.5 μm. The separator made of the lithium titanium aluminum phosphate layer with this thickness improves the cycle capacity retention rate of the battery, which can be as high as 97.7%, while ensuring the mechanical properties.

[0060] The second aspect of the present application provides a diaphragm, including a base film, a lithium titanium aluminum phosphate layer, a ceramic layer and a first adhesive layer, the lithium titanium aluminum phosphate layer is coated on one side of the base film, and the ceramic layer is coated on the other side of the base film; the lithium titanium aluminum phosphate layer is located between the base film and the first adhesive layer, and the lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 70% to 90% of lithium titanium aluminum phosphate particles, 5% to 15% of a conductive agent and 5% to 15% of an adhesive.

[0061] The lithium aluminum titanium phosphate layer in the separator of the present application not only has the advantages of high ion conductivity and wide electrochemical window, but also has good heat resistance and mechanical strength, which can improve the battery safety performance while taking into account the battery electrical performance.

[0062] The diaphragm of the present application also includes a first adhesive layer, and the lithium titanium aluminum phosphate layer is located between the base film and the first adhesive layer. Compared with the lithium titanium aluminum phosphate layer directly contacting the electrode, adding the first adhesive layer on the surface of the lithium titanium aluminum phosphate layer can make the battery diaphragm and the negative electrode more tightly combined after hot pressing, and the inside of the winding core is smoother, which improves the safety performance while also ensuring the manufacturability and electrical performance of the battery cell.

[0063] The diaphragm of the present application can reduce the coating thickness while ensuring the performance of the battery cell, ensuring the electrolyte retention amount of the long-cycle battery cell, thereby improving the electrical performance of the battery.

[0064] The diaphragm of the present application improves the overall tensile strength of the battery diaphragm. The diaphragm is pulled to both sides at the moment of needle puncture, which reduces the short-circuit area in the positive and negative electrodes to a certain extent. Moreover, the diaphragm of the present application improves the heat shrinkage resistance of the diaphragm, further reducing the short-circuit area. In addition, the diaphragm of the present application also has excellent ionic conductivity and chemical stability, can work stably in high temperature environment, and has excellent battery cell rate performance and long-term cycle performance.

[0065] Furthermore, the first adhesive layer is coated in a single layer, that is, the lithium titanium aluminum phosphate layer is first coated on one side of the base film, and then the first adhesive layer is coated.

[0066] In some embodiments, the lithium aluminum titanium phosphate particles are lithium aluminum titanium phosphate nanoparticles.

[0067] In some embodiments, the lithium aluminum titanium phosphate layer has a thickness of 1 μm to 2.5 μm.

[0068] In some embodiments, the ceramic layer includes the following components in percentage by weight: 65% to 82% ceramic, 3% to 10% conductive agent, and 15% to 25% binder. With this composition and its percentage by weight, the ceramic coating has a small thickness and low internal resistance, and an excellent needle penetration rate and cycle capacity retention rate are obtained, thereby improving the safety and electrical performance of the battery.

[0069] In some embodiments, the separator also includes a second binder layer, the ceramic layer is located between the base film and the second binder layer, and the ceramic layer includes the following components in percentage by weight: 87% to 94% ceramic, 1% to 3% conductive agent, and 5% to 10% binder. Adding a second binder layer on the surface of the ceramic layer can make the battery separator and the electrode more tightly combined after hot pressing, and the inside of the winding core is smoother, which improves safety performance while ensuring the manufacturability and electrical performance of the battery cell.

[0070] In some embodiments, the thickness of the ceramic layer is 1 μm to 3 μm. When mixed and coated, the thickness of the ceramic layer can be controlled to be 1 μm to 3 μm, which not only reduces the internal resistance, but also reduces the coating thickness while ensuring the performance of the battery cell, leaving room for the electrolyte retention of the long-cycle battery cell.

[0071] As an example, the thickness of the ceramic layer can be 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm and 3.0μm, or it can be within the range formed by any two of the above point values ​​as end values.

[0072] In some embodiments, the thickness of the ceramic layer is 2 μm to 4 μm. When the separator is provided with a second adhesive layer, the thickness of the ceramic layer can be controlled to be 2 μm to 4 μm.

[0073] In some embodiments, the thickness of the first adhesive layer is 0.5 μm to 2 μm.

[0074] As an example, the thickness of the first adhesive layer can be 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm and 2.0μm, or it can be within the range consisting of any two of the above point values ​​as end values.

[0075] In some embodiments, the thickness of the second adhesive layer is 0.5 μm to 2 μm.

[0076] As an example, the thickness of the second adhesive layer can be 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm and 2.0μm, or it can be within the range consisting of any two of the above point values ​​as end values.

[0077] In some embodiments, the material used in the first binder layer is the same as the binder in the lithium titanium aluminum phosphate layer.

[0078] In some embodiments, the second binder layer is made of the same material as the binder in the ceramic layer.

[0079] In some embodiments, the material of the first adhesive layer includes one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid and polyvinyl alcohol.

[0080] In some embodiments, the material of the second adhesive layer includes one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid and polyvinyl alcohol.

[0081] In some embodiments, the ceramic component includes one or more of alumina, boehmite, magnesium hydroxide, calcium hydroxide or silicon dioxide.

[0082] In some embodiments, the base film material includes one or both of polyethylene (PE) and polypropylene (PP).

[0083] Furthermore, the base film is a PE base film, a PP base film or a PP / PE / PP composite base film.

[0084] The third aspect of the present application provides a method for preparing a diaphragm, comprising the following steps:

[0085] Calculated by mass percentage, 40% to 70% of lithium aluminum titanium phosphate particles, 3% to 15% of a conductive agent and 25% to 50% of a binder are mixed and coated on one side of the base film to form a lithium aluminum titanium phosphate layer.

[0086] Understandably, mixed coating means increasing the mass content of the binder, mixing the binder with lithium aluminum titanium phosphate particles and the conductive agent, and coating them on the surface of the base film together as a lithium aluminum titanium phosphate layer. Although a very small amount of binder is also used in the positive electrode sheet, negative electrode sheet or coating of traditional batteries, its role is to bond the powder inside the electrode or the powder inside the coating, and it does not play the role in this application.

[0087] The mixed coating method is used to prepare the lithium titanium aluminum phosphate layer, which can not only improve the coating efficiency of the coating, but also reduce the coating thickness, thereby reducing the diaphragm impedance and improving the electrical performance of the battery. Moreover, after reducing the coating thickness, the liquid retention space is increased, which is beneficial to ensure the electrolyte retention volume for long cycles and further improve the electrical performance of the battery.

[0088] A fourth aspect of the present application provides a method for preparing a diaphragm, comprising the following steps:

[0089] 70% to 90% of lithium aluminum titanium phosphate particles, 5% to 15% of a conductive agent, and 5% to 15% of a binder are coated together on one side of the base film in terms of mass percentage to form a lithium aluminum titanium phosphate layer;

[0090] Then, a binder is coated on the surface of the lithium aluminum titanium phosphate layer to form a first binder layer.

[0091] A first adhesive layer is added to the surface of the lithium titanium aluminum phosphate layer of the diaphragm, and the lithium titanium aluminum phosphate layer is located between the base film and the first adhesive layer. Compared with the direct contact between the lithium titanium aluminum phosphate layer and the electrode, adding the first adhesive layer on the surface of the lithium titanium aluminum phosphate layer can make the battery diaphragm and the negative electrode more tightly combined after hot pressing, and the inside of the winding core is smoother, which improves the safety performance while ensuring the manufacturability and electrical performance of the battery cell.

[0092] In some of the embodiments, the method for preparing the diaphragm further includes the following steps: by weight percentage, 65% to 82% of ceramic, 3% to 10% of a conductive agent, and 15% to 25% of a binder are mixed and coated on the other side of the base film as a ceramic layer.

[0093] Understandably, mixed coating means increasing the mass content of the binder, mixing the binder with the ceramic and the conductive agent, and coating them together on the other surface of the base film as a ceramic layer. Although a very small amount of binder is also used in the positive electrode sheet, negative electrode sheet or coating of traditional batteries, its role is to bond the powder inside the electrode or the powder inside the coating, and it does not play the role in this application.

[0094] In some embodiments, the method for preparing the diaphragm further includes the following steps: coating 87% to 94% of ceramic, 1% to 3% of a conductive agent, and 5% to 10% of a binder on one side of the base film in terms of mass percentage to form a ceramic layer;

[0095] Then, a binder is coated on the surface of the ceramic layer to form a second binder layer.

[0096] The fifth aspect of the present application provides a battery, comprising a positive electrode sheet, a negative electrode sheet, and a diaphragm as described in the first aspect or the second aspect and a diaphragm prepared by the preparation method as described in the third aspect or the fourth aspect, wherein the diaphragm is located between the positive electrode sheet and the negative electrode sheet.

[0097] The batteries include, but are not limited to, lithium-ion batteries, lead-acid batteries, nickel-metal hydride batteries, and lithium polymer batteries.

[0098] In some embodiments, the method for preparing a lithium battery comprises the following steps:

[0099] 1) The positive electrode slurry is evenly coated on both sides of the substrate, and the positive electrode sheets are obtained by rolling and slitting; the positive electrode slurry includes a positive electrode active material, a positive electrode conductive agent and a positive electrode adhesive; the substrate is aluminum foil.

[0100] 2) The negative electrode slurry is evenly coated on both sides of the substrate, and the negative electrode sheet is obtained by rolling and cutting; the negative electrode slurry includes a negative electrode active material, a negative electrode conductive agent and a negative electrode adhesive; the substrate is a copper foil;

[0101] 3) The positive electrode sheet, the negative electrode sheet and the separator described in the first aspect are assembled and wound, the tabs are welded and packaged in an aluminum-plastic film, baked at 75°C-85°C, and then non-aqueous electrolyte is injected, sealed, formed and capacity divided to finally obtain a lithium battery.

[0102] In some embodiments, the positive electrode active material is one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium manganese-rich material, lithium nickel cobalt aluminum oxide and lithium titanate.

[0103] In some embodiments, the positive electrode conductive agent is one or more of acetylene black, Ketjen black, graphene, and carbon nanotubes.

[0104] In some embodiments, the positive electrode binder is one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, and polyurethane.

[0105] In some embodiments, the negative electrode active material is one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon oxygen, silicon carbon, silicon-based alloy, and lithium titanate.

[0106] In some embodiments, the negative electrode conductive agent is one or more of acetylene black, Ketjen black, graphene, carbon nanotubes, and conductive carbon black.

[0107] In some embodiments, the negative electrode binder is one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, conductive polymer polyacrylonitrile, hydroxymethyl chitosan, polyacrylic acid, and polyvinyl alcohol.

[0108] In some embodiments, the electrolyte is lithium hexafluorophosphate, lithium tetrafluoroborate or lithium bis(fluorosulfonyl)imide electrolyte.

[0109] The sixth aspect of the present application provides an electrical device comprising the battery as described in the fifth aspect.

[0110] The following are specific embodiments.

[0111] Example 1

[0112] A diaphragm: lithium titanium aluminum phosphate particles, graphene conductive agent and binder PVDF are fully mixed in a mass ratio of 85%:10%:5%, sprayed on one side of a base film to form a lithium titanium aluminum phosphate layer 1 with a thickness of 1 μm, and vacuum dried at 60°C; after drying, a binder is sprayed on the surface of the lithium titanium aluminum phosphate layer 1, and dried at 60°C to form a first binder layer 4 with a thickness of 1 μm; boehmite, conductive agent graphene and binder PVDF are mixed in a mass ratio of 90%:2%:8%, sprayed on the other side of the base film, and dried to form a ceramic layer 2 with a thickness of 2 μm; a layer of binder PVDF is coated on the surface of the ceramic layer 2 to form a second binder layer 5 with a thickness of 1 μm, and a diaphragm is prepared. The diaphragm structure is as follows: Figure 1 shown.

[0113] The positive electrode sheet, the above-mentioned separator and the negative electrode sheet are wound into a battery cell, the first adhesive layer 4 of the above-mentioned separator corresponds to the negative electrode sheet, and the side where the second adhesive layer 5 is located corresponds to the positive electrode sheet, and then the final lithium-ion battery is obtained by liquid injection, packaging, formation, capacity division and other methods.

[0114] Example 2

[0115] Example 2 is basically the same as Example 1, except that when the positive electrode sheet, the above-mentioned separator and the negative electrode sheet are wound into a battery cell, the side where the first adhesive layer 4 is located corresponds to the positive electrode sheet, and the side where the second adhesive layer 5 is located corresponds to the negative electrode sheet.

[0116] Example 3

[0117] Example 3 is basically the same as Example 1, except that the lithium titanium aluminum phosphate particles, graphene conductive agent and binder PVDF are fully mixed in a mass ratio of 56%:4% and 40%:, and the mixture is coated on one side of the PE base film to form a lithium titanium aluminum phosphate layer with a thickness of 2 μm, and the surface of the lithium titanium aluminum phosphate layer is no longer coated with a binder as a bonding layer.

[0118] Example 4

[0119] Example 4 is basically the same as Example 3, except that the thickness of the lithium aluminum titanium phosphate layer is 1.5 μm.

[0120] Example 5

[0121] The lithium aluminum titanium phosphate particles, graphene conductive agent and binder PVDF were fully mixed in a mass ratio of 56%:4% and 40%:, mixed and coated on one side of the PE base film 3 to form a lithium aluminum titanium phosphate layer 1 with a thickness of 2 μm, and vacuum dried at 60°C; on the other side of the diaphragm, boehmite, conductive agent and binder were mixed and coated in a mass ratio of 82:10:25 to form a ceramic layer 2 with a thickness of 3 μm, and a diaphragm was prepared. The diaphragm structure is as follows: Figure 2 shown.

[0122] The positive electrode sheet, the above-mentioned separator and the negative electrode sheet are wound into a battery cell, the ceramic layer corresponds to the positive electrode sheet, and the lithium aluminum titanium phosphate layer corresponds to the negative electrode sheet, and then the final lithium-ion battery is obtained through methods such as liquid injection, packaging, formation, and capacity division.

[0123] Example 6

[0124] Example 6 is basically the same as Example 3, except that: the lithium titanium aluminum phosphate particles, the graphene conductive agent and the binder PVDF are fully mixed in a mass ratio of 65%:5%:30%; and the thickness of the lithium titanium aluminum phosphate layer is 2 μm.

[0125] Example 7

[0126] Implementation 7 is basically the same as Implementation 3, except that: the lithium titanium aluminum phosphate particles, the graphene conductive agent and the binder PVDF are fully mixed in a mass ratio of 50%:12%:38%; and the thickness of the lithium titanium aluminum phosphate layer is 2 μm.

[0127] Example 8

[0128] Example 8 is basically the same as Example 1, except that: the lithium titanium aluminum phosphate particles, graphene conductive agent and binder PVDF are fully mixed in a mass ratio of 75%:15%:10%; the thickness of the lithium titanium aluminum phosphate layer is 1 μm.

[0129] Example 9

[0130] Example 9 is basically the same as Example 1, except that: the lithium titanium aluminum phosphate particles, graphene conductive agent and binder PVDF are fully mixed in a mass ratio of 80%:5%:15%; the thickness of the lithium titanium aluminum phosphate layer is 1 μm.

[0131] Comparative Example 1

[0132] The lithium aluminum titanium phosphate particles are fully mixed with the graphene conductive agent and the binder PVDF in a mass ratio of 85%:10%:5%, and sprayed on one side of the PE base film to form a lithium aluminum titanium phosphate layer 1 with a thickness of 1 μm; boehmite, conductive agent graphene and binder PVDF are mixed in a mass ratio of 90%:2%:8%, sprayed on the other side of the base film, and dried to form a ceramic layer 2 with a thickness of 2 μm. After drying, a layer of binder PVDF is coated on the surface of the ceramic layer 2 to form a second binder layer 5 with a thickness of 1 μm, thereby obtaining a diaphragm. The diaphragm structure is as follows: Figure 3 shown.

[0133] The positive electrode sheet, the above-mentioned separator and the negative electrode sheet are wound into a core, the lithium titanium aluminum phosphate layer 1 of the above-mentioned separator corresponds to the negative electrode sheet, and the side where the second adhesive layer 5 is located corresponds to the positive electrode sheet, and then the final lithium-ion battery is obtained by liquid injection, packaging, formation, capacity division and other methods.

[0134] Comparative Example 2

[0135] Comparative Example 2 is basically the same as Example 1, except that the lithium titanium aluminum phosphate layer is omitted, a binder layer (PVDF, 1 μm) is coated on one side of the base film, and the other side is the same as Comparative Example 1 to obtain a diaphragm. The diaphragm structure is as follows: Figure 4 shown.

[0136] The positive electrode sheet, the above-mentioned separator and the negative electrode sheet are wound into a battery cell, the side where the first adhesive layer 4 of the above-mentioned separator is located corresponds to the negative electrode sheet, and the side where the second adhesive layer 5 is located corresponds to the positive electrode sheet, and then the final lithium-ion battery is obtained by methods such as liquid injection, packaging, formation, and capacity division.

[0137] Comparative Example 3

[0138] Comparative Example 3 is substantially the same as Example 1, except that the ceramic layer is omitted.

[0139] Comparative Example 4

[0140] Comparative Example 4 is basically the same as Example 3, except that the lithium titanium aluminum phosphate particles, graphene conductive agent and binder PVDF are fully mixed in a mass ratio of 15%:5%:80%, mixed and coated on one side of the PE base film to form a lithium titanium aluminum phosphate layer with a thickness of 2 μm, and the surface of the lithium titanium aluminum phosphate layer is no longer coated with a binder as a bonding layer.

[0141] The lithium ion cells prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were subjected to a needle puncture test, and the prepared lithium ion batteries were subjected to a cycle test.

[0142] Battery cell puncture test method: Fix the battery on the puncture device, arrange the temperature sensing wire on the battery surface, and connect the voltage detection wire to monitor the temperature and voltage changes during the puncture process. Refer to the method in GB / T31485-2015, use a steel needle with a diameter of 5-8mm and a sharp angle of 45-60°, and pierce perpendicular to the large surface at a speed of (25±5)mm / s. Preferably, the steel needle has a diameter of 5mm, an angle of 45°, and a puncture speed of 25mm / s.

[0143] Battery cycle test method: The battery rated power is P, and it is charged to the cut-off voltage at constant power with nP power (n=0.33, 0.5, 1), and then discharged to the cut-off voltage at constant power for cycling. The preferred n=0.5, 0.5P constant power charge and discharge cycle.

[0144] The coating thickness, base film thickness and performance test results of the battery separators in Examples 1 to 9 and Comparative Examples 1 to 4 are shown in Tables 1 and 2 below.

[0145] Table 1

[0146]

[0147] Table 2

[0148]

[0149] As can be seen from Table 1 above, it can be seen from the results of Example 1 and Comparative Example 1 that when the PVDF binder layer is omitted on one side of the diaphragm, the processability of the diaphragm is poor, the cycle performance of the manufactured battery cell is poor, and the safety performance is reduced. The diaphragm of Comparative Example 2 does not have a lithium titanium aluminum phosphate coating, the mechanical strength of the diaphragm decreases, the internal short circuit phenomenon is more serious during the acupuncture process, the acupuncture pass rate is significantly reduced, and the cycle capacity retention rate is reduced. Comparative Example 3 removes the boehmite coating, and the safety performance and electrochemical performance of the battery cell are slightly reduced, but not as good as the impact of the lithium titanium aluminum phosphate layer on the safety performance. Comparative Example 4 shows that when the components of the lithium titanium aluminum phosphate layer are not within the scope of this application, the mechanical strength of the mixed coating is insufficient, the safety performance is reduced, and the cycle capacity retention rate is not greatly affected, and the lithium titanium aluminum phosphate can still play a role in improving the electrical performance.

[0150] Figure 5 , Figure 6 and Figure 7 The negative electrode interface of the battery cell in the fully charged state is shown in Figure 1. The separators prepared in Example 1, Example 3 and Comparative Example 1 are used respectively. It can be seen that the negative electrode interface of the battery cell made of the separator without PVDF layer in Comparative Example 1 is poor, and the purple spots are more and denser (please refer to Figure 7 ), while the negative electrode of the battery cell with PVDF layer separator in Example 1 has fewer purple spots and a better interface (see Figure 5), Example 3 uses a mixed coating layer, which can still achieve the effect of less purple spots and good interface (see Figure 6 ).

[0151] from Figure 8 It can be seen that in the case of comparative example 2 without the lithium titanium aluminum phosphate coating, when the needle puncture test began, a serious internal short circuit occurred when the steel needle punctured the battery cell, the voltage dropped rapidly, and the heat inside the battery cell accumulated rapidly. However, in the case of the battery cell made of the separator with the lithium titanium aluminum phosphate layer in Example 1, during the needle puncture test, the voltage dropped slowly and the battery temperature gradually rose, thus avoiding serious thermal runaway and improving the safety of the battery.

[0152] from Fig. 9 It can be seen that the lithium titanium aluminum phosphate layer of Example 1 improves the performance of the battery cell on the negative electrode side more than that of Example 2. When there is no PVDF layer on the surface of the lithium titanium aluminum phosphate of Comparative Example 1, the lithium titanium aluminum phosphate layer directly contacts the negative electrode surface, and the cycle retention rate decreases. The PVDF layer on the surface of the diaphragm makes the negative electrode and the diaphragm contact more closely, shortens the ion transmission path, and improves the cycle performance.

[0153] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0154] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A diaphragm, characterized in that: It includes a base film, a lithium titanium aluminum phosphate layer and a ceramic layer, wherein the lithium titanium aluminum phosphate layer is coated on one side of the base film, and the ceramic layer is coated on the other side of the base film; The lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 40% to 70% of lithium titanium aluminum phosphate particles, 3% to 15% of a conductive agent, and 25% to 50% of a binder.

2. The diaphragm according to claim 1, characterized in that The lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 45% to 65% of lithium titanium aluminum phosphate particles, 4% to 15% of a conductive agent, and 30% to 50% of a binder.

3. The diaphragm according to claim 1, characterized in that The thickness of the lithium aluminum titanium phosphate layer is 1 μm to 3 μm.

4. A diaphragm, characterized in that: It includes a base film, a lithium titanium aluminum phosphate layer, a ceramic layer and a first adhesive layer, wherein the lithium titanium aluminum phosphate layer is coated on one side of the base film, and the ceramic layer is coated on the other side of the base film; the lithium titanium aluminum phosphate layer is located between the base film and the first adhesive layer, and the lithium titanium aluminum phosphate layer includes the following components in percentage by mass: 70% to 90% of lithium titanium aluminum phosphate particles, 5% to 15% of a conductive agent and 5% to 15% of an adhesive.

5. The diaphragm according to claim 4, characterized in that The thickness of the lithium aluminum titanium phosphate layer is 1 μm to 2.5 μm.

6. The diaphragm according to any one of claims 1 to 5, characterized in that: The ceramic layer includes the following components in percentage by mass: 65% to 82% of ceramic, 3% to 10% of conductive agent and 15% to 25% of binder.

7. The diaphragm according to any one of claims 1 to 5, characterized in that: The diaphragm also includes a second adhesive layer, the ceramic layer is located between the base film and the second adhesive layer, and the ceramic layer includes the following components in percentage by mass: 87% to 94% of ceramic, 1% to 3% of conductive agent and 5% to 10% of adhesive.

8. The diaphragm according to claim 6, characterized in that The thickness of the ceramic layer is 1 μm to 3 μm.

9. The diaphragm according to claim 7, characterized in that The thickness of the ceramic layer is 2 μm to 4 μm.

10. The diaphragm according to claim 4 or 5, characterized in that The thickness of the first adhesive layer is 0.5 μm to 2 μm.

11. The diaphragm according to claim 7, characterized in that The thickness of the second adhesive layer is 0.5 μm to 2 μm.

12. The diaphragm according to claim 4 or 5, characterized in that The material of the first adhesive layer includes one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid and polyvinyl alcohol.

13. The diaphragm according to claim 7, characterized in that The material of the second adhesive layer includes one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid and polyvinyl alcohol.

14. A method for preparing a diaphragm, characterized in that: The following steps are involved: In terms of mass percentage, 40% to 70% of lithium aluminum titanium phosphate particles, 3% to 15% of a conductive agent and 25% to 50% of a binder are mixed to form a lithium aluminum titanium phosphate layer.

15. A method for preparing a diaphragm, characterized in that: The following steps are involved: 70% to 90% of lithium aluminum titanium phosphate particles, 5% to 15% of a conductive agent, and 5% to 15% of a binder are coated together on one side of the base film in terms of mass percentage to form a lithium aluminum titanium phosphate layer; Then, a binder is coated on the surface of the lithium aluminum titanium phosphate layer to form a first binder layer.

16. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and a separator as claimed in any one of claims 1 to 13 and a separator prepared by the preparation method as claimed in claim 14 or 15, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.

17. An electrical device, characterized in that: Comprising the battery of claim 16.